Cetacean Skeletons Demonstrate Ecologically Relevant Variation in Intraskeletal Stable Isotopic Values - Smith, Kerri J.; Sparks, Jed P.; Timmons, Zena L.; Peterson, Markus J. (Frontiers in Marine Science, 2020)
Conservation science requires quickly acquiring information and taking action in order to protect species at risk of extinction. Stable isotope measurements are one way to rapidly gather data regarding species’ foraging ecology and habitat use, and passively collected samples limit additional stress to at-risk species. For these samples to be useful, however, we must know how representative they are of the stable isotope ratios of the entire organism. Bone tissue, often stored in museum collections or research centers, may be the most readily available tissue from rare, endangered, or extinct vertebrates, but using bone requires practitioners to understand intraskeletal stable isotope variation. We sampled the same eight skeletal elements from 72 cetacean skeletons from 14 species to evaluate intraskeletal variation in carbon and nitrogen isotope values. We found considerably more variation than anticipated. Carbon intraskeletal ranges varied from 0.4 to 7.6‰, with 84.7% (n = 61) of skeletons having a range >1‰, and 55.5% (n = 40) exhibiting a range >2‰. Similarly, nitrogen intraskeletal ranges varied from 0.4 to 5.2‰, with 59.7% (n = 43) of skeletons exhibiting a range >1‰, and 15.3% (n = 11) with a range >2‰. There were differences in which bones contributed most to intraskeletal variation; however, we advise against using humeri and mandibles as these bones presented the most consistent trends in deviation from the intraskeletal means for both isotopes. The large intraskeletal variation we observed is likely due to changes in foraging behavior or habitat use being reflected differently in bone isotope ratios due to differences in bone turnover rates. We suggest that for cetaceans, intraskeletal carbon isotope ranges >1‰ and nitrogen ranges >2‰ are ecologically relevant, and that using different bones from animals of the same population may produce false positive differences in foraging behavior or habitat within the population if intraskeletal variation is not considered. Future studies should use the same bones from each animal and conduct species-specific analyses of intraskeletal variation, if possible, when using specimens of opportunity. Failure to consider this variation could lead to erroneous conclusions regarding a species range or key habitats, jeopardizing conservation efforts.